The Benefits of Alternatives to Conventional College: Comparing the Labor-Market Returns to For-Profit Schools and Community Colleges - Christopher Jepsen; Peter Mueser; Kenneth Troske; Kyung-Seong Jeon (Center for Economic Studies and ifo Institute (CESifo), 2021)
This paper provides novel evidence on the labor-market returns to for-profit postsecondary school and community college attendance using a two-step model to avoid recent concerns with singlestage fixed effects methods. Specifically, we link administrative records on for-profit school and community college attendance with quarterly earnings data for over 400,000 students in one state. Five years after enrollment, quarterly earnings conditional on employment exceed earnings in the absence of schooling by 20-29 percent for students attending for-profit schools and 16-27 percent for students attending community colleges. Despite differences in costs, in aggregate the benefits of attendance generally exceed the costs in both for-profit schools and community colleges. Finally, we present evidence showing that students in for-profit schools and community colleges pursue different degrees and focus on different areas of study.
Keywords: J24; I26; 330; postsecondary education; labor-market returns; for-profit schools